Fear trumps the common good: Psychological antecedents of vaccination attitudes and behaviour - Adamus, Magdalena; Čavojová, Vladimíra; Mikušková, Eva Ballová (Acta psychologica, 2022)
The study investigated antecedents of attitudes towards vaccines against COVID-19 and vaccination behaviour, and sought to identify areas where interventions aimed at increasing vaccination rates would be most effective. A sample of 500 Slovaks (250 women) responded to questions concerning their socio-demographic and personality characteristics, collectivism and individualism, consciousness of future consequences, and emotional responses to both vaccination and the pandemic. The study indicates that helplessness related to the vaccine efficacy evaluation and fear of its potential risks are the strongest antecedents of vaccination behaviour and anti-vaccination attitudes. Jointly with the fear of the COVID-19, they explained over 26% and 33% of variance in behaviour and attitudes, respectively. The results indicate that the efficiency of appeals to solidarity may be limited when fear and helplessness are widespread as they seem to strongly outweigh individuals' outward motivations to get vaccinated.
Keywords: vakcinace; Attitude; Fear; strach; lidé; sociální spravedlnost; Female; Vaccination; postoj; SARS-CoV-2; COVID-19 Vaccines; Social Justice; vakcíny proti COVID-19; COVID-19; ženské pohlaví; Humans